Genetic Diversity of Merozoite Surface Protein 2 (MSP2) Plasmodium falciparum Clinical Isolate in Wamena General Hospital - Dirk Y.P. Runtuboi; Rosye H.R. Tanjung; Yulius Sarungu; Meidy J. Imbiri; Irma A. Resmol; Ign. Joko Suyono (Jurusan Biologi FMIPA Universitas Cenderawasih, 2020)
The genetic diversity of typical clinical isolated Plasmodium falciparum in the malaria population varies greatly, especially at the location where malaria disease were recorded at high incidence rate. MSP2 is known as glycoprotein expressed on the surface of merozoites, which is an antigenic protein and has a potential to act as vaccine candidate for malaria. The MSP2 gene has two main allelic groups called FC27 and 3D7/IC. Block 3 from MSP2 gene is the most polymorphic to describe the diversity of parasite populations. The P. falciparum parasite population is often characterized by wide genetic diversity in areas of high transmission intensity. Therefore, the study on P. falciparum diversity is useful to describe the level of malaria transmission. The study of genetic diversity focused on clinical isolated species at Wamena General Hospital was aimed to determine the presence of the MSP2 gene, variety of MSP2 gene allele and the dominant frequency of the MSP2 gene allele. This research has been carried out from March 2018 to February 2019 using a cross sectional approach. The research sample was taken and prepared from Wamena Regional Hospital and followed by the analyzing of DNA isolation, PCR, electrophoresis of the research samples was done at the genetic science laboratory in Jakarta, Indonesia. The samples studied were patients who met the inclusion criteria, namely a single P. falciparum infection with an asexual parasite density >1000 parasites/µl or >3+ (1-10 P/Lp), and were agreed to become respondents by signing an informed consent. A total of 26 clinical isolates of P. falciparum were isolated with the MSP2 gene distribution on the FC27 allele with the highest as many as 25 samples (96.2%), 22 samples (84.6%) of the 3D7 / IC allele while the mixture of the two alleles was 22 samples (84.6%). From a total of 26 samples, there were samples with the male gender category counted for 77.3% and female 41%. The results of the identification of clinical isolated P. falciparum at Wamena Hospital with a total of 26 samples were found in productive age, between 15-34 years with a single allele (95.8%), while 23 cases and mix (both alleles 87.5%) about 21 cases, meanwhile in cases of before-productive age, in which ages were 12 and 14 years of age with a single allele 100% (FC27) 2 cases and 50% (3D7/IC) found to be 1 case, The mixture of the two alleles is 50% was only 1 case and there was no sample at non-productive age observed. Key words: Malaria; MSP-2; P. falciparum; Wamena